Priručnici inostranih univerziteta i zavoda u nastavi srpskog kao stranog jezika nakon Drugog svetskog rata (Philologia, 2024)
This paper analyzes the digital holdings of foreign libraries to identify various manuals published after the Second World War. The goal is to create a comprehensive register of manuals that have not yet been included in bibliographies, while also examining their role and significance in the teaching of Serbian as a foreign language during that period. The study employs the method of theoretical analysis, combined with content analysis techniques. The research results show that the 1970s, 1980s, and 1990s were the most productive decades in terms of creating and publishing instructional materials. In addition to textbooks and grammars, which represent the core components of instructional materials, particular attention was given to the publication of various types of manual dictionaries – pictorial dictionaries, conversational language dictionaries, and dictionaries of the most common words and phrases – all of which were distinguished by their specific didactic-methodical design. These manuals were primarily published by Western European and American universities, institutes, and schools for the purpose of teaching Serbo-Croatian as a foreign language. However, there were also manuals intended for travelers in Serbian regions who sought to communicate with the local Serbian-speaking population.
Keywords: Serbian as a Foreign Language; library funds; textbook set; manuals; dictionaries